The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12864-018-5158-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of long non-coding RNAs involved in the early somatic embryogenesis in Dimocarpus longan Lour

Abstract: BackgroundLong non-coding RNAs (lncRNAs) are involved in variable cleavage, transcriptional interference, regulation of DNA methylation and protein modification. However, the regulation of lncRNAs in plant somatic embryos remains unclear. The longan (Dimocarpus longan) somatic embryogenesis (SE) system is a good system for research on longan embryo development.ResultsIn this study, 7643 lncRNAs obtained during early SE in D. longan were identified by high-throughput sequencing, among which 6005 lncRNAs were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 74 publications
2
20
0
Order By: Relevance
“…Moreover, 68.22% of the lncRNAs contained only one exon, whereas 85.98% of the mRNAs comprised more than two exons. These observations are consistent with the findings of studies on maize (Li et al, 2014), kiwifruit (Tang et al, 2016), and longan (Chen et al, 2018a), which confirmed that lncRNAs contain fewer exons than the annotated mRNAs and that most plant lncRNAs contain one exon.…”
Section: Sequencing and Assembly Of Transcriptome Datasupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, 68.22% of the lncRNAs contained only one exon, whereas 85.98% of the mRNAs comprised more than two exons. These observations are consistent with the findings of studies on maize (Li et al, 2014), kiwifruit (Tang et al, 2016), and longan (Chen et al, 2018a), which confirmed that lncRNAs contain fewer exons than the annotated mRNAs and that most plant lncRNAs contain one exon.…”
Section: Sequencing and Assembly Of Transcriptome Datasupporting
confidence: 92%
“…In Arabidopsis thaliana, the lncRNA IPS1, which is an eTM of ath-miR399, can inhibit the cleavage of PHO2 by ath-miR399 (Franco-Zorrilla et al, 2007). Similarly, several lncRNAs function by interacting with miRNAs in other plant species (Hao et al, 2015;Wang et al, 2015;Deng et al, 2018;Chen et al, 2018a). Furthermore, nta-eTMX27 in Nicotiana tabacum , osa-eTM160 in Oryza sativa (Wang et al, 2017a), lncRNA23468 in Solanum lycopersicum (Jiang et al, 2019), and LTCONS-00042843 in Dimocarpus longan (Chen et al, 2018a) are eTMs that modulate target gene expression by functioning as decoys for relevant miRNAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with the findings in maize [3], kiwifruit [68] and longan [12], the lncRNAs contains fewer exons than annotated mRNAs and the majority of the lncRNAs in plants are single exon transcripts.…”
Section: Sequencing and Assembly Of Transcriptome Datasupporting
confidence: 91%
“…The mRNAs, miRNAs and lncRNAs qRT-PCR was performed by the LightCycler 480 platform (Roche Applied Sciences, Basel, Switzerland) with Transtart Tip Green qPCR SuperMix (TransGen Biotech, Beijing, China), respectively. The setting of qRT-PCR procedure and reaction system were both referred to the method of Chen et al [12]. The glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and β-actin genes were used as reference genes for mRNAs and lncRNAs normalization.…”
Section: Relative Expression Analyses Of the Selected Lncrnas Mrnasmentioning
confidence: 99%